Will I Fit in and Do Well? The Importance of Social Belongingness and Self-Efficacy for Explaining Gender Differences in Interest in STEM and HEED Majors. - Tellhed, Una; Bäckström, Martin; Björklund, Fredrik (Sex Roles, 2017)
Throughout the world, the labor market is clearly gender segregated. More research is needed to explain women's lower interest in STEM (Science, Technology, Engineering and Mathematics) majors and particularly to explain men's lower interest in HEED (Health care, Elementary Education, and the Domestic spheres) majors. We tested self-efficacy (competence beliefs) and social belongingness expectations (fitting in socially) as mediators of gender differences in interest in STEM and HEED majors in a representative sample of 1327 Swedish high school students. Gender differences in interest in STEM majors strongly related to women's lower self-efficacy for STEM careers and, to a lesser degree, to women's lower social belongingness expectations with students in STEM majors. Social belongingness expectations also partly explained men's lower interest in HEED majors, but self-efficacy was not an important mediator of gender differences in interest in HEED. These results imply that interventions designed to lessen gender segregation in the labor market need to focus more on the social belongingness of students in the gender minority. Further, to specifically increase women's interest in STEM majors, we need to counteract gender stereotypical competence beliefs and assure women that they have what it takes to handle STEM careers.